A low RCS wideband high gain CP slot antenna loaded with frequency selective surface - Verma, Hridesh Kumar (2021)
In this paper, a compact wideband circularly polarized slot antenna consisting of two L-shaped resonators is proposed. The slot antenna is loaded with a band-stop frequency selective surface (FSS) reflector to improve the gain of the antenna and to reduce the profile of the antenna. The radiation and scattering characteristics of FSS loaded slot antenna are compared with the metallic reflector loaded slot antenna, and the proposed antenna shows improved impedance bandwidth of 1.75–2.65 GHz. The measured results show that the peak gain of the slot antenna with FSS is enhanced by 4 dB. The proposed antenna with FSS also exhibits 3-dB ARBW of 2.2–2.65 GHz, and the scattering performance shows an average RCS reduction of 7.34 dB is achieved by slot antenna with FSS as compared to slot antenna with metallic reflector with peak RCS reduction of 24 dB at 1.2 GHz.